The Application of Logistics Robot in the Solution of Locating Route Problems in Trans CAD - Tan, Chaoying; Li, Panke (Informatica, 2025)
Intelligent production enterprises globally are advancing smart vehicles, necessitating improved location-transport routing for multi-robot systems. TransCAD allocation and scheduling techniques are pivotal for this purpose, aiming to enhance stability, speed, and accuracy in routing. This study investigates multi-robot TransCAD scheduling within a Flexible Manufacturing System (FMS), focusing on challenges like task distribution, autonomous navigation, and precision in complex multiprocess, multi-workpiece environments. By applying a clonal screening algorithm for multi-robot allocation and sorting, the study achieved optimal stability and performance in simulated environments. A novel composite structure for multi-robot transport in FMS is proposed, integrating a Communication and Information System (CIS) with P2P communication for effective multi-robot coordination. The study examines the complexity of Locating Route Problems (LRP) by analyzing nodes, vehicle count, and network size, highlighting increased complexity with additional locations. Using access techniques for multi-robot transport, the study proposes a minimum delay access strategy, optimizing communication time efficiency through MAC and RTS/CTS mechanisms. Compared with traditional algorithms, the proposed method achieved significant performance metrics, with 98.5% accuracy, 97.8% precision, and 98.2% recall, demonstrating its effectiveness in multi-robot transport.